تطبيق استراتيجية التعليم"الخريطة الذهنية" لرفع حماسة الطلاب ونتيجة تعلمهم في درس النحو العربي - Yoke Suryadarma; Rizqi Fitriasari; Fazlur Rachman (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
After conducting the observation, the researcher found some students' problems in understanding Nahwu lesson, especially for the third grade. It was also found that students' enthusiasm declines in the process of teaching Nahwu in the classroom. Hence, the researcher wanted to provide Teaching solutions using the mind mapping strategy to raise students' enthusiasm and the result of their learning. In this strategy, the researcher did not make any products of mind mapping, but used the mind mapping process as the kind of strategy which had been conducted by the researcher. The aim of this research is to reveal the increase in students' enthusiasm and the result of their learning. The data came from the result of students' enthusiasm in the class and the result of their learning. This research based on the Classroom Action Research using Kemmis and Mc. Taggart model. After applying two cycles of the teaching in the class, doing the observation as well as the reflection which the researcher did the result’s comparison between the first cycle of teaching and the second one, the researcher obtained that the mind map strategy is able to raise students' enthusiasm and the result of their learning. Based on the aforementioned results, the researcher suggested that the mind mapping strategy could be used primarily in the Nahwu lesson.